돼지 유행성 설사병 바이러스의 스파이크 유전자 발현 형질전환 고구마 - 양경실(Kyoung Sil Yang); 임순(Soon Lim); 권석윤(Suk Yoon Kwon); 곽상수(Sang Soo Kwak); 김현수(Hyun Soo Kim); 이행순(Haeng (Journal of plant biotechnology, 2005)
Porcine epidemic diarrhea virus (PEDV) causes acute enteritis in pigs of all ages and is often fatal for neonates. In order to develop sweetpotato plants expressing PEDV antigen, we constructed the vector expressing spike gene of PEDV under the control of sweetpotato sporamin promoter or constitutive CaMV 35S promoter. The spike protein region of PEDV was synthesized by PCR and linked to each promoter, Transgenic sweetpotato [Ipomoea batatas (L.) Lam. cv. Yulmi] plants were developed from embryogenic calli following Agrobacterium tumefaciens-mediated transformation. The co-cultured embryogenic calli transferred to selective MS medium containing 1 mg/L 2,4-D, 100 mg/L kanamycin, and 400 mg/L claforan. These embryogenic calli were subcultured to the same selection medium at 3 weeks interval. Kanamycin-resistant calli transferred to hormone-free MS medium with kanamycin gave rise to somatic embryos and then converted into plantlets in the same medium. Southern blot analysis confirmed that the spike gene of PEDV was inserted into the genome of the sweetpotato plants. RT-PCR revealed that the spike gene of PEDV was highly expressed in transgenic sweetpotato plants. Porcine epidemic diarrhea virus (PEDV)는 돼지의 급성장염을 유발하여 설사 증상을 일으키는 바이러스이다. 본 연구에서는 고구마 저장뿌리 고발현 sporamin 프로모터 및 CaMV 35S promoter를 이용하여 PEDV 항원단백질을 생산하는 고구마 식물체를 개발하고자 하였다. 형질전환 벡터를 제작하기 위하여 PEDV에서 항원성이 알려진 스파이크 단백질의 일부분을 암호화하는 유전자를 PCR로 합성하였다. 고구마 [Ipomoea batatas (L.) Lam] 율미 품종의 배발생 캘러스를 재료로 하여 Agrobacterium tumefaciens을 매개로 형질전환하였다. 선발배지 (MS medium, 1 mg/L 2,4-D, 100 mg/L kanamycin, and 400 mg/L claforan)에서 배발생 캘러스를 3주 간격으로 4개월 동안 계대배양하여 카나마이신 저항성 캘러스를 선발하였다. 선발된 배발생 캘러스를 호르몬을 제거한 배지로 옮겨 체세포배를 유도하였으며 이후 shoot과 뿌리가 형성되었다. 재분화된 소식물체를 대상으로 PCR 분석으로 카나마이신 저항성 재분화 개체의 50% 이상이 도입 유전자를 가지고 있었으며 이들 식물체를 대상으로 Southern blot 분석하여 PEDV 유전자가 고구마 식물체의 게놈으로 안정적으로 도입되었음을 확인하였다. 형질전환 식물체에서 도입유전자의 발현을 RT-PCR로 분석한 결과 PEDV의 spike 유전자가 높은 수준으로 발현하였다.